Planetary backup bearings for high speed applications and service life estimation methodology - Lukas QUURCK (The Japan Society of Mechanical Engineers, 2017)
Backup bearings (BB) limit the translational movement of rotors during malfunction, overload or power loss in the active magnetic bearings (AMB) in order to enable safe spin down and reduce secondary damage. Especially for high speed applications like flywheels with high rotor inertia, the requirements towards the load capacity and service life of the BB is comparably high. For a special type of flywheel with exceptionally high speeds in the BB interface, a planetary BB system is presented. The planetary BB consists of multiple bearing units placed circumferentially around the stator. Its elastic properties are described as well as a contact damping model. For cost efficient BB investigation, a scaled test rig is introduced and a parametric study of different delevitation simulations is done. Several quantification methods to evaluate severity, bearing loads and lifetime utilization during rotor delevitations are presented and applied to the simulations. Using a dry friction model a service life estimation of MoS2 ball bearing lubrication is made. The applicability of the planetary BB to vertical high speed rotors is confirmed by the simulation data and bearing element selection is affirmed. The results of the quantification methodologies show specific correlation to initial conditions and parameters like unbalance and in particular friction coefficient. Further the influence of the rotor weight and size to the bearing loads is investigated.